The Role of KH. Fakhrurrazi in the Field of Hadith in Ogan Ilir Regency, South Sumatra - Muhammad Adriansyah Rum; Uswatun Hasanah; Sulaiman M. Nur (CV. Doki Course and Training, 2024)
Ulama are people who play an important role in the lives of Muslims, starting from asking questions about things related to religion to solving social problems in society. There are quite a lot of scholars who have or possess very high levels of knowledge, but not many people recognize and know these scholars, as is the case with KH. Fakhrurrazi. This research aims to find out the role of KH. Fakhrurrazi in the field of hadith in Ogan Ilir Regency, South Sumatra. This research was conducted using qualitative methods and field research, as well as data analysis using descriptive-analytical analysis. The research results show that the role of KH. Fakhrurrazi in the field of hadith is reflected in his pious and productive personality in writing ahkam hadith books. The writing of this book was specifically used as a means to make things easier for the students and the people of Seribandung village who studied with it. Apart from that, the ahkam hadith he wrote was also aimed at people who really needed explanations of hadiths that discussed the law at that time to provide new insights. Although KH. Fakhrurrazi only re-copied the books contained in Kutub al-Sittah, but the results of his work had a significant impact on society, namely changing the pattern of life of the community with regard to the practices of muamalah law. This is a major contribution by KH. Fakhrurrazi in his time studying hadith, considering the limitations and developments of the times, which were not like today.